Patient‐reported symptoms and experience following Guillain‐Barré syndrome and related conditions: Questionnaire development and validation. (1st October 2021) - Siriwardena, Aloysius Niroshan; Akanuwe, Joseph N. A.; Botan, Vanessa; Laparidou, Despina; Curtis, Ffion; Jackson, Jennifer; Asghar, Zahid B.; Hodgson, Timothy L.
Abstract: Background: Guillain‐Barré syndrome (GBS) is a rare inflammatory peripheral nerve disorder with variable recovery. Evidence is lacking on experiences of people with GBS and measurement of these experiences. Objective: We aimed to develop and validate an instrument to measure experiences of people with GBS. Design: We used a cross‐sectional design and online self‐administered questionnaire survey. Question domains, based on a previous systematic review and qualitative study, covered experiences of GBS, symptom severity at each stage, healthcare and factors supporting or hindering recovery. Descriptive, exploratory factor and reliability analyses and multivariable regression analysis were used to investigate the relationships between variables of interest, explore questionnaire reliability and validity and identify factors predicting recovery. Setting and Participants: People with a previous diagnosis of GBS were recruited through a social media advert. Results: A total of 291 responders, of different sexes, and marital statuses, were included, with most diagnosed between 2015 and 2019. Factor analysis showed four scales: symptoms, i nformation provided, f actors affecting recovery and c are received . Positive social interactions, physical activity including physiotherapy and movement, changes made at home and immunoglobulin treatment were important for recovery. Multivariable models showed that immunoglobulin and/or plasma exchange were significant predictors of recovery. Employment and recovery factors (positive interactions, work support and changes at work or home, physical activity and therapy), though associated with recovery, did not reach statistical significance. Conclusion: The questionnaire demonstrated good internal reliability of scales and subscales and construct validity for people following GBS. Patient Contribution: Patients were involved in developing and piloting the questionnaire.